The Capacity of Farmers in Rice Farming in Kabupaten Lampung Tengah - Muher Sukmayanto; Tubagus Hasanuddin; Indah Listiana (Universitas Muhammadiyah Malang, 2022)
Rice is an important commodity and the availability of rice supply in Indonesia must be maintained, because rice is the staple food of the Indonesian people which must always be fulfilled at all times. However, the fact is that the average productivity of rice produced by farmers is still low. Low rice productivity reflects the capacity of farmers in rice farming. The aims of this research are: (1) to know the level of farmer's capacity? and (2) to find out what factors that affect the capacity of farmers. This research was conducted in Kabupaten Lampung Tengah with the number of respondents as many as 100 farmers. The data analysis method used is multiple regression analysis. The results showed that the level of farmer's capacity was in the medium category. Factors that have a significant effect on farmer’s capacity are farmer’s’ age, farming experience, farmer’s motivation, community support, farmer group support, and agricultural extension support, while formal education, non-formal education, cosmopolitan level, land area, and family support have no significant effect on the capacity of farmers in rice farming.